Carbon Nanotubes and Similar Nanostructures Derived from Biomass for Supercapacitors Application - Duygun, İnal Kaan; Çelik Bedeloğlu, Ayşe (Springer Science and Business Media Deutschland GmbH, 2023)
Carbon nanotubes are advanced carbon materials with unique physicochemical and mechanical properties that make them important candidates for supercapacitor applications. However, their synthesis mostly requires carbon precursors derived from fossil fuel-related compounds. Recently, the use of biomass as a carbon source for energy storage materials has attracted great attention. Biomass precursors are considered an alternative carbon source to fossil fuel-related compounds in energy storage devices. In this section, the importance of biomass-based carbon nanotubes, their composites, and similar nanostructures for supercapacitor applications is evaluated. The potential use and common applications of biomass-based carbon nanotubes for high-performance SC applications are assessed. The synthesis methods for carbon nanotubes from biomass precursors are presented. A future perspective of biomass-derived carbon nanotubes and the fabrication of high-performance supercapacitors are also discussed. © 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.
Keywords: Biomass; Carbon nanostructures; Carbon nanotubes; Supercapacitors